Knowledge, perceptions, and behavioral responses to earthquake early warning in Aotearoa New Zealand - Vinnell, Lauren Jennifer; Tan, Marion Lara; Prasanna, Raj; Becker, Julia Susan (Frontiers in Communication, 2023)
Aotearoa New Zealand (NZ) experiences frequent earthquakes, with a history of damaging and fatal events, but currently does not have a national, official earthquake early warning (EEW) system. Since April of 2021, Google’s Android Earthquake Alert System has operated independently in NZ. While recent work has identified general public support for such a system, it is important to assess public knowledge of EEW as well as typical responses to receiving an alert. The protective actions “Drop, cover, and hold” are recommended and taught in NZ and previous research found strong intentions to undertake these and other protective actions in response to an alert. However, it is important to explore a range of responses to these novel EEWs, including how much people know about them, what actions they took in response to the warning, and their overall judgment of the system including its usefulness. We undertook surveys following two widely received alerts from the Android Earthquake Alert System to assess public knowledge, perceptions, and responses to these alerts with a total sample size of 3,150. While most participants who received the alert found it useful, knowledge of both EEW generally and the Android System was low and few participants used the time to protect themselves from shaking. These findings reiterate the importance of education and communication around a warning system, so that the public know how to act when they receive an alert.